Pathogens and toxins in foods : challenges and interventions - Juneja, Vijay K., 1956-; Sofos, John Nikolaos (ASM Press, 2010)
Pathogens and Toxins in Foods: Challenges and Interventions offers a farm-to-table approach to food safety that enables readers to control microbial pathogens and toxic agents at all stages of the food supply chain. The book begins with chapters that help readers understand the characteristics of specific pathogens and toxins, the illnesses they cause, and the factors such as food processing operations that affect their survival and growth in food products. Further, the chapters in the book explore the most recent advances in biological, chemical, and physical interventions to control food-borne hazards during pre-harvest, harvest, food processing, and in retail ready-to-eat foods and food service operations. Also included are chapters that discuss the latest methods to rapidly detect food-borne pathogens as well as the implementation of comprehensive food safety management systems. Each chapter has been written by one or more leading experts in the field of food safety. Their advice is based on a thorough investigation of the literature as well as their own first-hand experience. In short, by drawing from hundreds of sources, this book offers food safety professionals a unique, single reference containing the latest understanding of food-borne hazards as well as the latest methods to detect and control their incidence. - Publisher.